Recovery-supportive interventions for people with substance use disorders: a scoping review - Sinclair, Deborah L.; Chantry, Mégane; De Ruysscher, Clara; Magerman, Jürgen; Nicaise, Pablo; Vanderplasschen, Wouter (Frontiers in Psychiatry, 2024)
Background: Recovery-supportive interventions and strategies for people with substance use disorders are a cornerstone of the emergent recovery paradigm. As compared to other services, such approaches have been shown to be holistically focused and improve outcomes (e.g. substance use, supportive relationships, social functioning, and well-being). Even so, a comprehensive overview of the nature, extent, and range of research on the topic is lacking. Methods: A scoping review of the literature was conducted to characterize the main topics on recovery-supportive interventions. A systematic search was conducted in three databases: Scopus, Web of Science, and PubMed from January 2000 to July 2023 using the PRISMA-ScR. Twenty-five studies published between 2005 -2022 met the inclusion criteria. Results: Most studies emanated from the United States, and we found a peak in publication frequency betweenin 2018-2022 (n = 13) relative to other years. The most prominent lines of inquiry appear to concern recovery-oriented policies; principles of recoveryoriented services (challenges encountered when implementing oriented-recovery-oriented practices, relationships with service providers characterized by trust, and service user-service provider collaboration), and recovery capital (particularly recovery-supportive networks, employment, and housing). Seventeen studies addressed co-occurring disorders, and eight addressed substance use recovery. Conclusions: To advance the field, more context-specific studies are required on supporting peer professionals, (including enabling cooperation with service users, and hiring experts by experience as staff), and training of professionals (e.g., nurses, psychologists, social workers, physicians) in the principles of recovery.